THE URGENCY OF PREPARING REGIONAL REBRANDING THAT INCLUDES DISASTER MITIGATION STRATEGIES IN INDONESIA - Eli Jamilah Mihardja; Prima Mulyasari Agustini; Sofia W Alisjahbana; Fatin Adriati (Universitas Djuanda Bogor, 2022)
Local Governments can make their own branding, as an identity and also the basis for regional marketing so that they can provide the maximum benefit for the community, nation and state. However, the branding strategy should also include disaster mitigation considering that Indonesia is a disaster-prone country. By ensuring disaster mitigation in the area's branding strategy, the community and visitors will feel relatively safe. This article is sourced from a research report through a grant from the Indonesian Ministry of Education and Culture. The research was conducted in Lombok in 2021 and continued in 2022 by also including benchmarking in the Toba and Yogyakarta regions. The results show that West Nusa Tenggara is relatively successful in establishing its regional branding with the theme of sport-tourism and is also currently including islands other than Lombok, However, the implementation of disaster mitigation has not yet been integrated into the branding plan